The Role of the Renin-Angiotensin System and Vitamin D in Keloid Disorder—A Review - Kilmister, Ethan J.; Paterson, Claudia; Brasch, Helen D.; Davis, Paul F.; Tan, Swee T. (Frontiers in Surgery, 2019)
Keloid disorder (KD) is a fibroproliferative condition characterized by excessive dermal collagen deposition in response to wounding and/or inflammation of the skin. Despite intensive research, treatment for KD remains empirical and unsatisfactory. Activation of the renin-angiotensin system (RAS) leads to fibrosis in various organs through its direct effect and the resultant hypertension, and activation of the immune system. The observation of an increased incidence of KD in dark-skinned individuals who are predisposed to vitamin D deficiency (VDD) and hypertension, and the association of KD with hypertension and VDD, all of which are associated with an elevated activity of the RAS, provides clues to the pathogenesis of KD. There is increasing evidence implicating embryonic-like stem (ESC) cells that express ESC markers within keloid-associated lymphoid tissues (KALTs) in keloid lesions. These primitive cells express components of the RAS, cathepsins B, D and G that constitute bypass loops of the RAS, and vitamin D receptor (VDR). This suggests that the RAS directly, and through signaling pathways that converge on the RAS, including VDR-mediated mechanisms and the immune system, may play a critical role in regulating the primitive population within the KALTs. This review discusses the role of the RAS, its relationship with hypertension, vitamin D, VDR, VDD, and the immune system that provide a microenvironmental niche in regulating the ESC-like cells within the KALTs. These ESC-like cells may be a novel therapeutic target for the treatment of this enigmatic and challenging condition, by modulating the RAS using inhibitors of the RAS and its bypass loops and convergent signaling pathways.